Transparent aligners: An invisible approach to correct mild skeletal class III malocclusion - A Arif Yezdani (Wolters Kluwer Medknow Publications, 2015)
This case report highlights the treatment of a mild skeletal class III malocclusion with an invisible thermoplastic retainer. A 15-year-old female patient presented with a mild skeletal class III malocclusion with a retrognathic maxilla, orthognathic mandible, a low mandibular plane angle with Angle's class III malocclusion with maxillary lateral incisors in anterior cross-bite with crowding of maxillary anteriors, imbricated and rotated mandibular incisors and deep bite. Accurate upper and lower impressions and a bite registration were taken with polyvinyl siloxane rubber base impression material. This was then sent to the lab for the processing of a series of ClearPath aligners. The ClearPath virtual set-up sent from the lab provided the treatment plan and interproximal reduction estimation complete with posttreatment results. This enabled the clinician to actively participate in the treatment plan and provide the necessary suggestions. The ClearPath three-dimensional aligner was found to have effectively corrected the anterior cross-bite and crowding of the maxillary anteriors.